Rectification of the position of the type locality of Brachycephalus tridactylus (Anura: Brachycephalidae), a recently described species from southern Brazil - Bornschein, Marcos R.; Belmonte-Lopes, Ricardo; Ribeiro, Luiz F.; Maurício, Giovanni Nachtigall; Pie, Marcio R. (Zootaxa, 2015)
The aim of this note is to correct the geographical position of the type locality of Brachycephalus tridactylus, a recently described species from southern Brazil (Garey et al. 2012). The type locality of B. tridactylus was designated as follows: “Serra do Morato (25°04’54”S; 48°19’53”W; 900–930 m above sea level; datum WGS84), Reserva Natural Salto Morato, municipality of Guaraqueçaba, state of Paraná” (Garey et al. 2012). However, when we plotted this locality data on Google Earth, the type locality was placed 6.80 km to the northwest of the Serra do Morato, falling on a different mountain range (with no common name) and outside Reserva Natural Salto Morato (FGBPN 2011). We therefore performed a fieldtrip to the exact point where the type series was collected (according to a local guide who participated in the collection of specimens with which the species was described). Using a GPS device (Garmin GPSmap 60CSx) we recorded the geographic coordinates and, after plotting this point on Google Earth, we recorded the altitude. We verified that the geographical coordinates of the type locality of B. tridactylus are: 25°08’09”S, 48°17’59”W (datum WGS84).